Ornamental Allium species - Benke, Ashwini P; Singh, Major (Indian Horticulture, 2019)
Allium is a very diverse genus, comprising about 700 species and presenting vast array of morphological traits. Besides edible and wild alliums, few species have become popular as an ornamental plants and introduced as commercial cut flowers for outdoor cultivation. This ornamental value is based on their attractive coloured multiflowered inflorescence (A. giganteum, A.aflatunense) or some have few large flowers per umble (A. moly), sometime accompanied with sweet odour (A. cyrilli) and, spectacular leaves (A. macleanii). Normally, bloomed inflorescence of individual flower head lasts 1 to 2 weeks or in some species for a month in dried form. Presently, Netherland leads world’s ornamental Allium market followed by Israel, France and Japan.